Dysphagia in Duchenne muscular dystrophy assessed by validated questionnaire. Issue 2 (8th March 2013) - Archer, Sally K.; Garrod, Rachel; Hart, Nicholas; Miller, Simon
Abstract Background Duchenne muscular dystrophy (DMD) leads to progressive muscular weakness and death, most typically from respiratory complications. Dysphagia is common in DMD; however, the most appropriate swallowing assessments have not been universally agreed and the symptoms of dysphagia remain under‐reported. Aims To investigate symptoms of dysphagia in DMD and to determine the potential of the validated Sydney Swallow Questionnaire (SSQ) to diagnose dysphagia in this patient group. Methods & Procedures Three participant groups completed the SSQ and the results were compared: nine DMD participants with dysphagia, six DMD participants without dysphagia and 12 healthy controls. Outcomes & Results The questionnaire scores for dysphagic DMD participants were significantly higher than for non‐dysphagic DMD participants (p = 0.039) and for healthy controls (p ≤ 0.001). The diagnostic ability of the questionnaire was good for detecting dysphagia in participants with DMD (receiver operating characteristic (ROC) area under the curve = 0.89, p = 0.013), with a cut‐off score of 224.5 (13.2%) giving a sensitivity of 0.78 and a specificity of 0.83 for determining dysphagia. Dysphagic participants rated time to eat a meal, swallowing hard food, swallowing thick liquids and needing to cough up or spit during meals with the highest severity of all questionnaire items. Results of the questionnaire by item are presented to inform the clinician of the symptoms of dysphagia in DMD. Conclusions & Implications DMD leads to pervasive symptoms of dysphagia. The simple SSQ is a clinically informative assessment tool for patients with DMD.